2015
DOI: 10.1007/s13277-015-4693-3
|View full text |Cite
|
Sign up to set email alerts
|

Research advances in HMGN5 and cancer

Abstract: High-mobility group nucleosome-binding domain 5 (HMGN5) is a new member of the high-mobility group N (HMGN) protein family that is involved in nucleosomal binding and transcriptional activation. It was first discovered in mouse, and recent studies found that the expressions of HMGN5 in many human cancers were also highly regulated, such as prostate, bladder, breast, and lung and clear cell renal cell carcinoma. Numerous reports have demonstrated that HMGN5 plays significant roles in many biological and patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 96 publications
0
19
0
Order By: Relevance
“…Our previous study found that HMGN5 is highly expressed in osteosarcoma tissues, and knockdown of HMGN5 inhibits migration and invasion of U-2 OS and Saos-2 cells [13]. HMGN5 plays a role in PI3K/AKT signaling pathway or MAPK/ERK signaling pathway [12]. In addition, Ji et al found that the expression level of HMGA1 mRNA and protein were significantly higher in the hypoxic environment [48].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our previous study found that HMGN5 is highly expressed in osteosarcoma tissues, and knockdown of HMGN5 inhibits migration and invasion of U-2 OS and Saos-2 cells [13]. HMGN5 plays a role in PI3K/AKT signaling pathway or MAPK/ERK signaling pathway [12]. In addition, Ji et al found that the expression level of HMGA1 mRNA and protein were significantly higher in the hypoxic environment [48].…”
Section: Discussionmentioning
confidence: 96%
“…HMGA and HMGB are related to tumor metastasis. In recent years, the function of HMGN in tumor invasion and metastasis has been extensively studied [12]. Studies have shown that HMGN5 plays an important role in the metastasis of prostate cancer [43], bladder cancer [44,45], kidney cancer [46], and breast cancer [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, high mobility group nucleosome-binding domain 5 (HMGN5) has been recognized as a cancer-related gene in several types of human cancer. [7] HMGN5, also named nucleosomebinding protein 1, is a typical member of the HMGN protein family and is localized at the xq13.3 region of the human genome. [8] HMGN5 protein is located in the nucleus and regulates gene transcription through interaction with nucleosomes.…”
Section: Introductionmentioning
confidence: 99%